Linked Open Social Signals - Mendes, Pablo N.; Passant, Alexandre; Kapanipathi, Pavan; Sheth, Amit P. (2010 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology, 2010)
In this paper we discuss the collection, semantic annotation and analysis of real-time social signals from micro blogging data. We focus on users interested in analyzing social signals collectively for sense making. Our proposal enables flexibility in selecting subsets for analysis, alleviating information overload. We define an architecture that is based on state-of-the-art Semantic Web technologies and a distributed publish-subscribe protocol for real time communication. In addition, we discuss our method and application in a scenario related to the health care reform in the United States.